Nanometer cold-rolled automobile sheet surface silane composite pretreatment agent and preparation method thereof
The nanotechnology-based silane composite pretreatment agent addresses the inefficiencies of traditional methods by enhancing adhesion and corrosion resistance, providing a stable and environmentally friendly solution for cold-rolled automobile sheets.
Patent Information
- Application Number
- CN202411210875.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2024-12-17
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional surface pretreatment methods for cold-rolled automobile sheets, such as pickling and phosphating, generate environmental pollution and are inefficient, failing to meet modern environmental and performance requirements.
A nanotechnology-based silane composite pretreatment agent is developed, comprising specific components and preparation steps, which form a stable coating that enhances adhesion and corrosion resistance, suitable for industrial production.
The silane composite pretreatment agent improves surface quality, provides strong adhesion and corrosion resistance, and extends the service life of coatings, offering an environmentally friendly and efficient solution.
Smart Images

Figure BDA0005020286360000061 
Figure BDA0005020286360000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal material surface treatment, and in particular relates to a nano cold-rolled automobile plate surface silane composite pretreatment agent and a preparation method thereof. Background Art
[0002] With the rapid development of the automobile industry, automobile sheets, as key materials in automobile manufacturing, have attracted more and more attention for their quality and performance. Cold-rolled automobile sheets are widely used in automobile bodies, engine hoods, doors and other parts due to their excellent mechanical properties and good formability. However, during the production, transportation and storage of cold-rolled automobile sheets, their surfaces are easily affected by factors such as oxidation, pollution and corrosion, resulting in a decrease in surface quality, which in turn affects the quality of subsequent coatings and the overall performance of the automobile. In order to improve the surface quality of cold-rolled automobile sheets, traditional surface pretreatment methods usually use processes such as pickling and phosphating. The pickling process can effectively remove oxides and pollutants on the surface of cold-rolled automobile sheets, but a large amount of waste acid and harmful gases will be generated during the treatment process, causing serious pollution to the environment. The phosphating process can form a phosphating film on the surface of cold-rolled automobile sheets to improve the adhesion and corrosion resistance of the coating, but the quality of the phosphating film is easily affected by process parameters and operating conditions, and phosphorus-containing wastewater will also be generated during the phosphating process, causing certain pollution to the environment. With the continuous improvement of environmental awareness and the increasingly stringent environmental regulations, traditional surface pretreatment methods such as pickling and phosphating can no longer meet the requirements of modern automobile industry for environmental protection and performance. Therefore, the development of a new, environmentally friendly and efficient surface pretreatment agent for cold-rolled automobile sheets and its preparation method has become an urgent problem to be solved in the current automobile industry. As an emerging technical means, nanotechnology has shown broad application prospects in the fields of materials science and environmental protection. Nanomaterials have unique physical and chemical properties, such as high specific surface area, high reactivity, excellent mechanical properties and thermal properties. The application of nanotechnology in the field of metal surface treatment can significantly improve the adhesion and corrosion resistance of the coating and extend the service life of the coating. As an environmentally friendly metal surface treatment agent, silane complex has good wettability, adhesion and corrosion resistance. Silane complex can react chemically with the metal surface to form a stable chemical bonding layer, thereby significantly improving the bonding force between the coating and the metal substrate. At the same time, silane complex also has good weather resistance and chemical corrosion resistance, which can protect the metal substrate from corrosion in harsh environments. Summary of the invention
[0003] The present invention combines nanotechnology with silane complexes, utilizes the high specific surface area and high reactivity of nanomaterials, uniformly disperses the silane complexes in a solvent, forms a stable pretreatment agent, and has a simple preparation method, is suitable for industrial production, overcomes the shortcomings of traditional surface pretreatment methods, and has the advantages of environmental protection, high efficiency, stability, etc. The pretreatment agent can not only improve the surface quality of cold-rolled automotive plates, but also provide good adhesion and corrosion resistance for subsequent coatings, extend the service life of the coatings, and provide a new solution for the development of the automotive industry.
[0004] In order to achieve the above-mentioned purpose of the invention, the present invention provides a silane composite pretreatment agent for the surface of a nano cold-rolled automobile sheet, wherein the surface silane composite pretreatment agent comprises the following components in parts by weight: 15 to 30 parts of a nano silane composite, 30 to 50 parts of an organic solvent, 0.5 to 3 parts of an acidic catalyst, 0.5 to 5 parts of a surfactant, 0.1 to 3 parts of a corrosion inhibitor, 0.1 to 3 parts of a stabilizer, 0.1 to 3 parts of a defoaming agent, 0.5 to 5 parts of a preservative, 0.5 to 5 parts of a complexing agent, 0.1 to 3 parts of a thickener, 0.1 to 2 parts of a dispersant, 0.1 to 3 parts of a pH regulator, and 55 to 75 parts of deionized water.
[0005] In the above technical solution, further, the nano-silane composite is prepared by mixing nano-silicon dioxide, aminosilane, epoxysilane, and methylsilane in a weight ratio of 2: (2-3): (2-3): 2, and the particle size of the nano-silicon dioxide is controlled to be 30-50 nm. These nano-silane composites can penetrate deeper into the microstructure of the metal surface, providing stronger adhesion and corrosion resistance.
[0006] The organic solvent is prepared by mixing ethanol, triisopropanol and toluene in a weight ratio of (5-6):3:1. The organic solvent is used to dilute the nano-silane composite to promote uniform coating.
[0007] The acidic catalyst is prepared by mixing sulfuric acid and phosphoric acid in a weight ratio of (6-7):3. The surfactant is prepared by mixing sodium dodecyl sulfate, a nonionic surfactant and an anionic surfactant in a weight ratio of (4-5):3:2. The acidic catalyst is used to adjust the pH value and promote the reaction of silane with the metal surface.
[0008] The surfactant is prepared by mixing sodium dodecyl sulfate, a nonionic surfactant and an anionic surfactant in a weight ratio of (4-5):3:2. The surfactant is used to reduce surface tension and improve wettability.
[0009] In addition, corrosion inhibitors, stabilizers, defoamers and preservatives are added to prevent metal corrosion, chelate metal ions, eliminate foam and inhibit bacteria and mold. Through reasonable agent selection and proportion control, the aim is to obtain a silane pretreatment agent with stable performance.
[0010] The corrosion inhibitor is prepared by mixing benzotriazole and zinc nitrate in a weight ratio of (2-3):2. The corrosion inhibitor is used to protect the metal surface and enhance the corrosion resistance.
[0011] The stabilizer is prepared by mixing polyvinyl pyrrolidone and carboxymethyl cellulose in a weight ratio of (6-7):3, and is used to improve the stability of the pre-treatment agent.
[0012] The defoamer is prepared by mixing an organic silicon defoamer and a polyether defoamer in a weight ratio of (3-4):1, and is used to eliminate foam generated during stirring and coating.
[0013] The preservative is prepared by mixing a kasson preservative and sodium benzoate in a weight ratio of (8-9):1. The preservative is used to inhibit the growth of microorganisms and prolong the service life.
[0014] The complexing agent is prepared by mixing ethylenediaminetetraacetic acid, nitrilotriacetic acid and diethylenetriaminepentaacetic acid in a weight ratio of (4-5):3:2. The complexing agent is used for complexing with metal ions to improve stability and corrosion resistance.
[0015] The thickener is prepared by mixing hydroxyethyl cellulose, carboxymethyl cellulose and polyacrylamide in a weight ratio of (5-6):3:1. The thickener is used to adjust viscosity and optimize coating performance.
[0016] The dispersant is prepared by mixing sodium polyacrylate, polyoxyethylene sorbitan fatty acid ester and polymethacrylate ammonium salt in a weight ratio of (4-5):3:2. The dispersant is used to enhance the dispersion stability of nanoparticles and other solids.
[0017] The pH regulator is prepared by mixing disodium hydrogen phosphate and sodium dihydrogen phosphate in a weight ratio of (6-7):3. The pH regulator is used to maintain a stable pH value and ensure consistency of treatment effects.
[0018] A method for preparing the above-mentioned nano cold-rolled automobile sheet surface silane composite pretreatment agent, the preparation method comprising the following steps:
[0019] ① Mixing of nano-silane complex and organic solvent: Add the nano-silane complex into the organic solvent according to the proportion, stir at a speed of 400 to 600 rpm, stir for 15 to 20 minutes, and keep the temperature at 55°C to 65°C.
[0020] ② Add auxiliary components: add the acid catalyst, surfactant and corrosion inhibitor to the mixture of step ① in order according to the proportion, increase the stirring speed to 600-800 rpm, the stirring time is 65-80 minutes, and the temperature is 65-75°C.
[0021] ③ Add the stabilizer, defoamer, preservative, complexing agent, thickener, dispersant, and pH adjuster: first add the complexing agent and pH adjuster to the mixture in step ② according to the formula ratio and adjust the stirring speed to 800-1000 rpm, then add the thickener and dispersant, increase the stirring speed to 1000-1200 rpm, and finally add the remaining additives, increase the stirring speed to 1800-2000 rpm for mixing. During the above operation, the stirring temperature is controlled at 75° C. to 85° C.;
[0022] ④ Add deionized water to the mixture obtained in step ③, adjust the total amount to the required number of portions, maintain the stirring speed at 1800-2000 rpm, and stir for 90-120 minutes to obtain a nano cold-rolled automobile sheet surface silane composite pretreatment agent.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The nanotechnology-based silane composite pretreatment agent for the surface of cold-rolled automobile plates of the present invention has become an efficient, environmentally friendly and practical innovative solution in the automobile industry with its high stability, strong adhesion and corrosion resistance, environmentally friendly and simple preparation method, and good versatility and adaptability. The method combines nanotechnology with silane complexes, utilizes the high specific surface area and high reactivity of nanomaterials, and evenly disperses the silane complexes in a solvent to form a stable pretreatment agent. The preparation method is simple and suitable for industrial production, overcoming the shortcomings of traditional surface pretreatment methods, and having the advantages of environmental protection, high efficiency, stability, etc. The pretreatment agent can not only improve the quality of the surface of cold-rolled automobile plates, but also provide good adhesion and corrosion resistance for subsequent coatings, extend the service life of the coating, and provide a new solution for automobile surface pretreatment technology. DETAILED DESCRIPTION
[0025] The present invention is further described below in conjunction with specific examples, but the present invention is not limited in any way. To avoid redundant description, the raw materials in the following examples are all commercially available products unless otherwise specified, and the methods used are all conventional methods unless otherwise specified.
[0026] A nano cold-rolled automobile sheet surface silane composite pretreatment agent comprises the following components in parts by weight: 15-30 parts of nano silane composite, 30-50 parts of organic solvent, 0.5-3 parts of acid catalyst, 0.5-5 parts of surfactant, 0.1-3 parts of corrosion inhibitor, 0.1-3 parts of stabilizer, 0.1-3 parts of defoamer, 0.5-5 parts of preservative, 0.5-5 parts of complexing agent, 0.1-3 parts of thickener, 0.1-2 parts of dispersant, 0.1-3 parts of pH regulator and 55-75 parts of deionized water.
[0027] A method for preparing the above-mentioned nano cold-rolled automobile sheet surface silane composite pretreatment agent, the preparation method comprising the following steps:
[0028] ① Mixing of nano-silane complex and organic solvent: Add the nano-silane complex into the organic solvent according to the proportion, stir at a speed of 400 to 600 rpm, stir for 15 to 20 minutes, and control the temperature at 55°C to 65°C.
[0029] ② Add auxiliary components: add the acid catalyst, surfactant and corrosion inhibitor to the mixture of step ① in order according to the proportion, increase the stirring speed to 600-800 rpm, the stirring time is 65-80 minutes, and the temperature is 65-75°C.
[0030] ③ Add the stabilizer, defoamer, preservative, complexing agent, thickener, dispersant, and pH adjuster: first add the complexing agent and pH adjuster to the mixture in step ② according to the formula ratio and adjust the stirring speed to 800-1000 rpm, then add the thickener and dispersant, increase the stirring speed to 1000-1200 rpm, and finally add the remaining additives, increase the stirring speed to 1800-2000 rpm for mixing. During the above operation, the stirring temperature is controlled at 75° C. to 85° C.;
[0031] ④ Add deionized water to the mixture obtained in step ③, adjust the total amount to the required number of portions, maintain the stirring speed at 1800-2000 rpm, and stir for 90-120 minutes to obtain a nano cold-rolled automobile sheet surface silane composite pretreatment agent.
[0032] The matters not described in the following embodiments are the same as the description of the above specific implementation methods.
[0033] Example
[0034] A nanometer cold-rolled automobile sheet surface silane composite pretreatment agent, the components and mass contents of the cold-rolled automobile sheet surface silane composite pretreatment agents of Examples 1-10 are shown in Table 1.
[0035] Table 1 Component ratio of silane composite pretreatment agent for cold-rolled automobile sheet surface of Examples 1-5
[0036]
[0037] A method for preparing the above-mentioned nano cold-rolled automobile sheet surface silane composite pretreatment agent, the specific process steps are:
[0038] ① Mixing of nano-silane complex and organic solvent: Add the nano-silane complex into the organic solvent according to the ratio, stir at a speed of 600 rpm, for 20 minutes, at a temperature of 65°C.
[0039] The nano-silane composite is prepared by mixing nano-silicon dioxide (particle size 30 nm), aminosilane, epoxysilane and methylsilane in a weight ratio of 2:3:3:2, and stirring at a stirring speed of 600 rpm for 20 minutes; the organic solvent is prepared by mixing ethanol, triisopropanol and toluene in a weight ratio of 6:3:1, and stirring at a stirring speed of 500 rpm for 10 minutes.
[0040] ② Add auxiliary components: add the acid catalyst, surfactant and corrosion inhibitor to the mixture in step ① in order according to the proportion, increase the stirring speed to 800 rpm, stir for 80 minutes, and keep the temperature at 75°C.
[0041] The acidic catalyst is prepared by mixing sulfuric acid and phosphoric acid in a weight ratio of 7:3, and stirring at a stirring speed of 400 rpm for 20 minutes; the surfactant is prepared by mixing sodium dodecyl sulfate, a nonionic surfactant and an anionic surfactant in a weight ratio of 5:3:2, and stirring at a stirring speed of 400 rpm for 20 minutes.
[0042] The corrosion inhibitor is prepared by mixing benzotriazole and zinc nitrate in a weight ratio of 3:2, and stirring the mixture at a stirring speed of 300 rpm for 25 minutes.
[0043] ③ Add the stabilizer, defoamer, preservative, complexing agent, thickener, dispersant, and pH adjuster: according to the formula ratio, first add the complexing agent and pH adjuster to the mixture in step ② and adjust the stirring speed to 1000 rpm, then add the thickener and dispersant, increase the stirring speed to 1200 rpm, and finally add the remaining additives, increase the stirring speed to 2000 rpm for mixing. During the above operation, the stirring temperature is controlled at 85°C.
[0044] The stabilizer is prepared by mixing polyvinyl pyrrolidone and carboxymethyl cellulose in a weight ratio of 7:3, and stirring the mixture at a stirring speed of 450 rpm for 25 minutes.
[0045] The defoamer is prepared by mixing a silicone defoamer and a polyether defoamer in a weight ratio of 4:1, and stirring at a stirring speed of 350 rpm for 15 minutes; the preservative is prepared by mixing a kason preservative and sodium benzoate in a weight ratio of 9:1, and stirring at a stirring speed of 300 rpm for 20 minutes.
[0046] The complexing agent is prepared by mixing ethylenediaminetetraacetic acid, nitrilotriacetic acid and diethylenetriaminepentaacetic acid in a weight ratio of 5:3:2, and stirring at a stirring speed of 400 rpm for 20 minutes. The thickening agent is prepared by mixing hydroxyethyl cellulose, carboxymethyl cellulose and polyacrylamide in a weight ratio of 6:3:1, and stirring at a stirring speed of 200 rpm for 30 minutes.
[0047] The dispersant is prepared by mixing sodium polyacrylate, polyoxyethylene sorbitan fatty acid ester and polymethacrylate ammonium salt in a weight ratio of 5:3:2, and stirring at a stirring speed of 400 rpm for 10 minutes; the pH adjuster is prepared by mixing disodium hydrogen phosphate and sodium dihydrogen phosphate in a weight ratio of 7:3, and stirring at a stirring speed of 400 rpm for 15 minutes.
[0048] ④ Add deionized water to the mixture obtained in step ③, adjust the total amount to the required number of portions, maintain the stirring speed at 2000 rpm, and stir for 120 minutes to obtain a silane composite pretreatment agent for the surface of a nano cold-rolled automotive sheet.
[0049] According to the above process flow, a nano cold-rolled automobile sheet surface silane composite pretreatment agent was prepared, and the test pieces were immersed in the nano cold-rolled automobile sheet surface silane composite pretreatment agent prepared in Examples 1-10, and the test pieces were taken out and tested for rust resistance according to SHT 0533 "Rust Assessment Method for Rust Test Pieces of Anti-Rust Grease". In addition, the contact angle of the silane composite pretreatment agent on the surface of the test piece was measured by the Sessiledrops method using a Dataphysics OCA50 fully automatic contact angle measuring instrument. The experimental temperature was room temperature, and a precision syringe was used to control the droplet volume of 4μl. The instrument measured an angle range of 0 to 180°, the video speed was 120 images per second, the measurement error was ±0.1°, and the average value was taken for multiple measurements. Because the surface tension spreads into a certain arc on the surface of the substrate, the software automatically calculates the contact angles on the left and right sides after selecting the reference plane. When the contact angles at both ends are close, the average value is taken as the wetting angle. Table 2 shows the implementation technology effects of the products obtained in Examples 1-10.
[0050] Table 2 Implementation technical effects of products obtained in Examples 1-10
[0051]
[0052] From the application technical effects of the products obtained by Examples 1-10 in Table 2, it can be seen that the pretreatment agent can not only improve the surface quality of cold-rolled automobile plates, but also provide good adhesion and corrosion resistance for subsequent coatings, extend the service life of the coatings, and provide a new solution for automobile surface pretreatment technology.
[0053] For any technician familiar with the art, without departing from the scope of the technical solution of the present invention, the technical content disclosed above can be used to make many possible changes and modifications to the technical solution of the present invention, or modified into equivalent embodiments with equivalent changes. Therefore, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention should still fall within the scope of protection of the technical solution of the present invention.
Claims
1. A silane composite pretreatment agent for the surface of nano cold-rolled automobile sheets, characterized in that: The composite pretreatment agent comprises the following components in parts by weight: 15 to 30 parts of nano-silane composite, 30 to 50 parts of organic solvent, 0.5 to 3 parts of acidic catalyst, 0.5 to 5 parts of surfactant, 0.1 to 3 parts of corrosion inhibitor, 0.1 to 3 parts of stabilizer, 0.1 to 3 parts of defoamer, 0.5 to 5 parts of preservative, 0.5 to 5 parts of complexing agent, 0.1 to 3 parts of thickener, 0.1 to 2 parts of dispersant, 0.1 to 3 parts of pH regulator and 55 to 75 parts of deionized water.
2. The surface silane composite pretreatment agent according to claim 1, characterized in that: The nano-silane composite is prepared by mixing nano-silicon dioxide, aminosilane, epoxysilane and methylsilane in a weight ratio of 2:(2-3):(2-3):2, and the particle size of the nano-silicon dioxide is controlled to be 30-50nm; the organic solvent is prepared by mixing ethanol, triisopropanol and toluene in a weight ratio of (5-6):3:
1.
3. The surface silane composite pretreatment agent according to claim 1, characterized in that: The acid catalyst is prepared by mixing sulfuric acid and phosphoric acid in a weight ratio of (6-7):3; the surfactant is prepared by mixing sodium dodecyl sulfate, a nonionic surfactant and an anionic surfactant in a weight ratio of (4-5):3:
2.
4. The surface silane composite pretreatment agent according to claim 1, characterized in that: The corrosion inhibitor is prepared by mixing benzotriazole and zinc nitrate in a weight ratio of (2-3):2; the stabilizer is prepared by mixing polyvinyl pyrrolidone and carboxymethyl cellulose in a weight ratio of (6-7):
3.
5. The surface silane composite pretreatment agent according to claim 1, characterized in that: The defoamer is prepared by mixing an organosilicon defoamer and a polyether defoamer in a weight ratio of (3-4):1; the preservative is prepared by mixing a Kathon preservative and sodium benzoate in a weight ratio of (8-9):
1.
6. The surface silane composite pretreatment agent according to claim 1, characterized in that: The complexing agent is prepared by mixing ethylenediaminetetraacetic acid, nitrilotriacetic acid and diethylenetriaminepentaacetic acid in a weight ratio of (4-5):3:2; the thickener is prepared by mixing hydroxyethyl cellulose, carboxymethyl cellulose and polyacrylamide in a weight ratio of (5-6):3:
1.
7. The surface silane composite pretreatment agent according to claim 1, characterized in that: The dispersant is prepared by mixing sodium polyacrylate, polyoxyethylene sorbitan fatty acid ester and polymethacrylate ammonium salt in a weight ratio of (4-5):3:2; the pH regulator is prepared by mixing disodium hydrogen phosphate and sodium dihydrogen phosphate in a weight ratio of (6-7):
3.
8. A method for preparing a silane composite pretreatment agent for the surface of a nano cold-rolled automobile sheet as claimed in claim 1, characterized in that: The preparation method comprises the following steps: ① Mixing of nano-silane complex and organic solvent: Add the nano-silane complex to the organic solvent according to the ratio, stir at a speed of 400 to 600 rpm, stir for 15 to 20 minutes, and control the temperature at 55°C to 65°C; ② Adding auxiliary components: Add the acidic catalyst, surfactant and corrosion inhibitor to the mixture in step ① in order according to the proportion, increase the stirring speed to 600-800 rpm, the stirring time is 65-80 minutes, and the temperature is 65-75° C.; ③ Add the stabilizer, defoamer, preservative, complexing agent, thickener, dispersant, and pH adjuster: first add the complexing agent and pH adjuster to the mixture in step ② according to the formula ratio and adjust the stirring speed to 800-1000 rpm, then add the thickener and dispersant, increase the stirring speed to 1000-1200 rpm, and finally add the remaining additives, increase the stirring speed to 1800-2000 rpm for mixing. During the above operation, the stirring temperature is controlled at 75° C. to 85° C.; ④ Add deionized water to the mixture obtained in step ③, adjust the total amount to the required number of portions, maintain the stirring speed at 1800-2000 rpm, and stir for 90-120 minutes to obtain a nano cold-rolled automobile sheet surface silane composite pretreatment agent.
Citation Information
Patent Citations
Zinc layer surface passivating treatment liquid
CN102586768A
Surface silane treatment agent of offshore drilling tool joint
CN103897584A
Metal surface treatment agent with silane coupling agents as main components and preparation method thereof
CN105441920A
Silane self-assembly treating agent for metal coating pretreatment and application of silane self-assembly treating agent
CN106637174A
Environment-friendly silane treating agent for metal coating pretreatment as well as preparation method and application of environment-friendly silane treating agent
CN117737717A
Cited By
Electric control liquid for intelligent coal mining equipment and preparation method of electric control liquid
CN120329998A
Epoxy coating maintenance agent as well as preparation method and application thereof
CN121930735A
An epoxy coating maintenance agent, its preparation method and application
CN121930735B
